Subclinical Hypothyroidism: Impact on Fertility, Obstetric and Neonatal Outcomes - Usadi, Rebecca S.; Merriam, Kathryn S. (Seminars in Reproductive Medicine, 2016)
The incidence of subclinical hypothyroidism (SCH) in pregnancy was classically thought to be low; however, with new definition of normal TSH range in pregnancy, there has been an increase in the percentage of women who meet classification for SCH. The diagnosis of SCH is important not only for monitoring for maternal conversion to overt hypothyroidism, but also for identifying obstetric and neonatal outcomes related to SCH. Although there have been proven associations between maternal overt hypothyroidism and adverse obstetric and neonatal outcomes, there has been conflicting data on the correlation between SCH and these outcomes. Recent data from a meta-analysis found an increased risk of pregnancy loss, placental abruption, premature rupture of membranes, and neonatal death for women with SCH compared to euthyroidism in pregnancy. Research studies have not demonstrated a distinct benefit from treatment of SCH, and the professional societies are divided on their recommendations for treating SCH. Additionally, universal screening of SCH is controversial at present.
Keywords: subclinical hypothyroidism; thryroid-stimulating hormone; thyroid peroxidase